Fostering morphological and semantic awareness through brand name creation: a task-based approach for Economics students - Wijayanti, Farida Indri; Asmara, Arif Yudi; Fatimah, Fatimah (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study explores the pedagogical potential of brand name creation in enhancing morphological and semantic awareness among Economics students. Employing a qualitative methodology within a task-based learning framework, the research engaged 120 students in a series of analytical and creative exercises involving both the deconstruction of existing brand names and the development of original, fictitious ones. The study draws on the morphological framework proposed by Tokar (2012) and the semantic typology outlined by Leech (1981), defining morphological awareness as the recognition and application of word-formation processes, and semantic awareness as the ability to interpret both conceptual and associative meanings. Findings indicate notable improvements in students' abilities to identify and utilize a range of morphological processes, including compounding, blending, borrowing, abbreviation, and clipping. Additionally, students exhibited increased sensitivity to semantic dimensions, especially in distinguishing and producing meanings that resonate with targeted consumer associations. A significant number of participants favored the use of eponyms in their brand name creations, citing their perceived positive connotations and stronger associative value. The study concludes that integrating brand name creation tasks into language learning for Economics students can serve as an effective strategy to cultivate linguistic competence, particularly in morphological construction and semantic interpretation. This approach not only reinforces theoretical understanding but also supports practical language application within entrepreneurial and business communication contexts.